Molecular Pathways in the Induction of Interleukin-27-Driven Regulatory Type 1 Cells - Pot, Caroline (Mary Ann Liebert, Inc., 2010)
Type 1 regulatory (Tr1) cells have emerged as key players in the prevention of autoimmunity. They produce high levels of the immunosuppressive cytokine interleukin (IL)-10 and confer protection against a wide panel of autoimmune diseases. However, the molecular pathways leading to their generation have long remained elusive. We have recently identified IL-27, a member of the IL-12 cytokine family, as a novel cytokine that induces Tr1 cells. Further analysis of IL-27-driven Tr1 cells have identified a critical role of the transcription factor avian musculoaponeurotic fibrosarcoma v-maf and of IL-21 in the generation of IL-27-induced Tr1 cells. Importantly, IL-27 also induces Tr1 cells in humans, suggesting that IL-27 administration may dampen tissue inflammation in humans as well. Here, we review the role of IL-27 in the generation of Tr1 cells and discuss its potential to alleviate autoimmune diseases.